Prognostic value of diabetes mellitus for acute type B intramural hematoma patients undergoing endovascular repair - Yu, Fumin; Miao, Miao; Wang, Bin; Xian, Haiying (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveThoracic endovascular aortic repair (TEVAR) is increasingly performed in patients with acute type B intramural hematoma (IMH). This study aimed to evaluate the effect of diabetes mellitus (DM) on postoperative clinical outcomes and aortic remodeling degree of acute type B IMH patients undergoing endovascular repair.MethodsWe retrospectively identified patients diagnosed with acute type B IMH at two medical centers between January 2017 and January 2024. Study subjects were divided into DM and none DM (nDM) groups. Baseline characteristics, procedure details, and postoperative outcomes were extracted for further analysis.ResultsForty-four patients were included in the study and were divided into DM (n = 12) and nDM groups (n = 32). Preoperative demographic characteristics, laboratory biomarkers, and imaging data were similar between the two groups. Compared with nDM group, the DM group presented a slightly higher rate of patients without postoperative major adverse events (MAE) (75.0% vs 68.8%, p = 0.651). At the 1-year follow-up, the DM group exhibited a significantly higher degree of aortic remodeling, as assessed by the TAD/TLD ratio [total aortic diameter [TAD] divided by the true lumen diameter [TLD] at the maximal IMH thickness] (DM group: 1.09 ± 0.04; nDM group: 1.17 ± 0.10, p = 0.032). Cox multivariate regression revealed that a TAD/TLD ratio > 1.32 increased the incidence of postoperative MAE significantly.ConclusionsDM is positively associated with the prognosis of patients with acute type B IMH undergoing TEVAR and promotes postoperative aortic remodeling. Moreover, a TAD/TLD ratio >1.32 independently predicts the incidence of postoperative MAE.